Respuesta :
Solve the second equation for y so that you can substitute it in for y in the first equation..
y = 5x - 4
Substitute:
3x + (5x - 4) = 1
y = 5x - 4
Substitute:
3x + (5x - 4) = 1
Answer:
3x + 5x - 4 = 1
Step-by-step explanation:
Given the equation
3x + y = 1
We must substitute the following equation:
y + 4 = 5x
So first we'll isolate y from the second equation so that then we can substitute its solution in the first equation:
y + 4 - 4 = 5x - 4
y = 5x - 4
Now we can substitute y in the first equation:
3x + y = 1
3x + 5x - 4 = 1